Modifikasi Perahu Jalur Menjadi Sarana Transportasi Pengangkut Barang - Zikri Zikri; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Transportation is needed by the people around the Riau inland rivers to bring agricultural and natural products to the market or to other places. The transportation needed by the community is a boat or boat capable of carrying goods in Riau's inland rivers which are relatively narrow, shallow and muddy. One of the river transportation used by the people of Riau is the lane boat, where this boat has proven reliable and resilient when operating in rivers that are narrow and muddy, but it needs modification and better design in order to be able to carry goods safely and optimally. The design begins by taking measurements directly to the lane boat and then using the comparison method the total length is 200 cm, width 50 cm and height 20 cm. The planned ship prototype has a reasonable shape and size and does not deviate from the provisions based on the calculation of the main size ratio of the ship. The ship design was made with the help of maxsurf software and obtained data in the form of hydrostatic parameters, resistance, stability and effective power. The prototype of this ship is operated by a remote control system and uses a 0.81 kw lawn mower engine. The test results show that the ship prototype has a good balance and complies with the criteria and requirements of the IMO (International Maritime Organization).The maximum carrying capacity of the ship is 16 kg with a speed of 1.46 m / s or 2.84 knots. From the test, the fuel consumption of the ship's engine shows the results are 0.21 mL / s when no load and when given a maximum load of 16 kg is 0.3 mL / s.Keywords: Line boat, ship prototype, ship power, ship speed.